The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages of the latter course argue that social agencies run by voluntary bodies are independent of local politics and therefore command greater respect, and that their workers are better trained and experienced than those which Local Authorities can supply. To this we would reply that an agency run by a national voluntary organisation is bound by the general policy of the association, and is not therefore really "independent,'' and there is no guarantee that the voluntary association will always follow a more enlightened policy, or a policy more in the interests of the people, than the Local Authority. Local Authorities are democratically elected and are therefore bound to give the people more or less what they want. As democracy develops, the influence of the electors on policy will increase, and there is every reason to hope that at the same time the interest of the general public in social services will grow, and services of a better and better quality will be demanded. If this is so, the influence of local public opinion should not be feared, but rather welcomed. While fully recognising the value of the pioneer work of the voluntary organisations, and realising that there is still much for them to do in studying social problems, carrying on educational work and propaganda, and raising professional standards, we believe that the interests of the people will best be served by encouraging local authorities to develop all their social services, including those needing 22 15X/2/464/1